From Alma Ata to the Global Fund: The history of international health policy - Italian Global Health Watch (Social Medicine Publication Group, 2024)
The paper traces the evolution of international health policies and international health institutions, starting from the birth of the World Health Organization, the setting up of the Health for All target at the Alma Ata conference in 1978 and the rise of neo-liberal policies promoted by international financial institutions from 1980 to the present. The paper looks at different issues surrounding public-private partnerships and the setting up of the Global Fund to fight AIDS, Tuberculosis and Malaria and the influence of these institutions on the health systems in poor countries.